THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN ORGANIZATIONAL CHANGE - Istiqomah, Istiqomah; Burhanuddin, Burhanuddin (International Research-Based Education Journal, 2022)
This study aims to determine the role of transformational leadership in organizational change. This study uses a literature review method from various previous research results that have been published. The results showed that transformational leadership has a positive and significant effect on the success of organizational change. In organizational change, transformational leaders act as motivators, directors, role models, and active participants in organizational change